INTEGRATING LEGAL AND SOCIOCULTURAL STRATEGIES TO ADDRESS WORKPLACE GENDER INEQUALITY IN PONTIANAK - Hazilina, Hazilina; Soedagoeng, Gembongseto Hendro (Faculty of Law, Universitas Tanjungpura, 2025)
Abstract This study explores the multifaceted issue of workplace gender inequality in Pontianak by integrating legal and sociocultural approaches to address the persistent challenges faced by women. Despite the presence of legal frameworks such as Law No. 13 of 2003 on Labor and Law No. 21 of 2007 on the Eradication of the Crime of Trafficking in Persons, enforcement remains inconsistent, and gender-specific barriers, such as the